Tourism Development Projects and Sustainable Livelihood Strategies in South Africa’s Rural and Urban Communities - Mnisi, PEARL THOBEKA; TLOU RAMOROKA (African Journal of Governance and Development, 2024)
Tourism development projects have been a prevalent instrument aiming at alleviating poverty in most rural and urban communities worldwide. Most of the implemented tourism development projects focused on the mutual understanding that community-based development assists areas in their determination towards incorporation into the national economy. Therefore, this paper seeks to assess the challenges and prospects of tourism development projects in sustaining the livelihood strategies of rural and urban communities in South Africa. This theoretical paper relied on existing literature to source out information. Scholarly journals and articles were used to solicit data to assess the challenges and prospects of tourism development projects in sustaining livelihoods in rural and urban communities of South Africa. The results have shown that tourism development projects contribute towards sustaining livelihoods strategies of rural and urban communities in South Africa. While on the other hand, the projects come with too many challenges, such as land degradation, pollution, straining of local infrastructure, and negative impacts on the livelihood strategies of urban residents. This paper concludes that while some tourism development initiatives overlook the sustainability of rural and urban communities' livelihood strategies, most of them aim at generating profit in the communities. Emanating from the challenges raised, the paper therefore recommends the need for all nature reserves representatives to promote tourism development projects that can sustain the livelihood strategies of the communities. Additionally, modified training should be offered, and tourism development projects should be considered as businesses where continuous monitoring and evaluation from investors or donors should be ensured.